From Physical Models to Innovations: Technology Advances in Architectural and Civil Engineering - Hassan Gbran (Universitas Sebelas Maret Surakarta, 2024)
This study delves into the profound impact of physical prototypes on engineering design. It explores their historical and ongoing relevance in advancing architectural and civil engineering. The author emphasizes the critical role of measurement prototypes in pioneering engineering endeavors, highlighting their importance in validating innovative designs and ensuring operational integrity and safety. Through illustrative examples from structural engineering and architectural acoustics, the study underscores the enduring significance of physical models in engineering innovation. It provides valuable insights into the symbiotic relationship between physical prototypes and engineering theory, shedding light on their multifaceted role in propelling engineering advancements. Ultimately, the analysis offers a nuanced understanding of the integral contribution of physical prototypes to the advancement of the engineering discipline